The Community Perception of Waste Management on The Belawan Coast, North Sumatra: Persepsi Masyarakat Terhadap Pengelolaan Sampah di Pesisir Belawan, Sumatera Utara - Hasibuan, Febya Rizki; Hariyadi, Sigid; Pratiwi, Niken Tunjung Murti (Habitus Aquatica, 2025)
The abundant natural potential in the Belawan coastal area has great opportunities for the development of various activities. In addition, the Belawan coastal area is also vulnerable to high pollution, especially because of its role in supporting the regional economy through sectors such as tourism, fisheries, transportation, and industry. Effective waste management is a special concern of the government along with maximum efforts in developing economic potential. Waste has become a global problem, especially in Indonesia with its increasing population growth. This research aims to analyze strategies for controlling pollution from waste in the Belawan coastal area. The method used is a Likert Scale to evaluate the community's perception of the issue of waste problems. On the economic aspect, the community assessed that waste management has not had a significant impact, but on the social aspect, waste management was rated positively with the highest score reaching 68,80 which was obtained on waste management activities that increased fraternal ties. The problem of low sanitation awareness is the main obstacle that requires solutions based on community participation in waste management.